Kepadatan Tikus di Wilayah Pelabuhan ASDP dan Speed Bulang Linggi Tanjung Uban Kabupaten Bintan Provinsi Kepualauan Riau - Kurnia, Risman; Diansafitri, Mutia; Yusuf, M. (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2024)
The implementation of a healthy port aims to create healthy port conditions. Rats are animals that have the ability to adapt well to human environments if these places can support their lives, one of which is a port. There are diseases that can be transmitted through mice such as Murine Typhus, Salmonellosis, Richettsial Pox, rabies and Trichinosis. The aim of the research was to determine the density of rats at ASDP Harbor and Speed Bulang Linggi Tanjung Uban, Bintan Regency. The type of research used in this research is quantitative with a cross-sectional design. The samples for this study were all rats trapped using live traps using purposive sampling. The instrument used in this research was 100 live traps. The data collection method is by observation and direct observation of objects. The results of installing live traps which were carried out for 7 days showed that the rat density level at ASDP Harbor was 7%, while the rat density at Bulang Linggi Speed Harbor was 4%, which means that these two ports do not meet the requirements for rat density. It is necessary to control rats by maintaining environmental sanitation in both port areas. By closing open water channels and cleaning up rubbish in the gutters.